The ED‐inpatient dashboard: Uniting emergency and inpatient clinicians to improve the efficiency and quality of care for patients requiring emergency admission to hospital. (4th September 2016) - Staib, Andrew; Sullivan, Clair; Jones, Matt; Griffin, Bronwyn; Bell, Anthony; Scott, Ian
Abstract: Patients who require emergency admission to hospital require complex care that can be fragmented, occurring in the ED, across the ED‐inpatient interface (EDii) and subsequently, in their destination inpatient ward. Our hospital had poor process efficiency with slow transit times for patients requiring emergency care. ED clinicians alone were able to improve the processes and length of stay for the patients discharged directly from the ED. However, improving the efficiency of care for patients requiring emergency admission to true inpatient wards required collaboration with reluctant inpatient clinicians. The inpatient teams were uninterested in improving time‐based measures of care in isolation, but they were motivated by improving patient outcomes. We developed a dashboard showing process measures such as 4 h rule compliance rate coupled with clinically important outcome measures such as inpatient mortality. The EDii dashboard helped unite both ED and inpatient teams in clinical redesign to improve both efficiencies of care and patient outcomes.